Katalog der in den Sammlungen der Abteilung Taxonomie der Insekten des Institutes für Pflanzenschutzforschung, Bereich Eberswalde (ehemals Deutsches Entomologisches Institut), aufbewahrten Typen - XIX (Coleoptera: Staphylinidae). - Gaedike, Hannelore (Contributions to Entomology = Beiträge zur Entomologie, 1981)
This is a catalogue of the types of the Coleoptera of Staphylinidae preserved in the collections of the Department of Taxonomy of Insects of the Institute of Plant Protection Research, Eberswalde (former Deutsches Entomologisches Institut).